Effects of self-assessment on self-regulated learning and self-efficacy: Four meta-analyses. (November 2017) - Panadero, Ernesto; Jonsson, Anders; Botella, Juan
Abstract: This meta-analytic review explores the effects of self-assessment on students' self-regulated learning (SRL) and self-efficacy. A total of 19 studies were included in the four different meta-analyses conducted with a total sample of 2305 students. The effects sizes from the three meta-analyses addressing effects on different measures of SRL were 0.23, 0.65, and 0.43. The effect size from the meta-analysis on self-efficacy was 0.73. In addition, it was found that gender (with girls benefiting more) and certain self-assessment components (such as self-monitoring) were significant moderators of the effects on self-efficacy. These results point to the importance of self-assessment interventions to promote students' use of learning strategies and its effects on motivational variables such as self-efficacy. Highlights: Self-assessment effects on self-regulated learning (SRL) and self-efficacy were explored. 19 studies (2305 students) were included in four different meta-analyses. Effects sizes from the three meta-analyses on SRL were 0.23, 0.65 and 0.43. The effect size from the meta-analysis on self-efficacy was 0.73.